Knowledge, Attitude and Practice of Patients towards Orthodontic Treatment: A Multi-centric Study - Shrestha, Rabindra Man; Bhattarai, Prakash; Dhakal, Jyoti; Shrestha, Sujita (Orthodontic Journal of Nepal, 2014)
Introduction: Patient’s perspective and cooperation on treatment procedure and service is very important to evaluate the management system and success of the orthodontic treatment. Objective: To assess knowledge, attitude and practice of Nepalese patients towards orthodontic treatment and to find the difference of perception between female and male patients. Materials & Method: A structured questionnaire comprising of fifteen questions in three sections was used among 536 orthodontic patients at eight orthodontic treatment centers. The knowledge, attitude and practice were assessed on Likert scale. The data were rescored based on positive, neutral or negative perceptions and depicted for a level. The difference in perception between female and male patients was tested using Mann-Whitney U test. Result: 85% of orthodontic patients possess good knowledge about ongoing orthodontic treatment; however about half of the patients are unaware about retainers. About 35% patients think that people wearing braces do not look good, 59% experience long waiting time, 25% feel time spent for procedure is inadequate and 68% believe orthodontic treatment is expensive; still 82% are happy about treatment outcome. Most of the patients brush and rinse more carefully, however 28.9% patients are careless about braces and 12.7% forget appointment dates. Conclusion: Nepalese orthodontic patients possess good knowledge about orthodontic treatment, however lack adequate attitude and practice towards the treatment. The practitioners should inform patients about retainers and be concerned about waiting time, procedure duration and cost of the treatment. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11304 Orthodontic Journal of Nepal Vol.4(1) 2014; 6-11